Translation and validation of the Swedish version of the Appearance Schemas Inventory-Revised and investigation of the modified three subscale structure in patients undergoing breast reconstruction - Linn Weick; Carolina Lunde; Emma Hansson (Journal of Plastic Surgery and Hand Surgery)
Breast cancer can lead to changes in appearance and subsequent concerns about body image. This study aimed to translate the body investment instrument, Appearance Schemas Inventory-Revised (ASI-R), to Swedish, and perform a validation in women who underwent mastectomy and were awaiting breast reconstruction. The instrument was translated, and its psychometric properties were investigated according to current guidelines. Three hundred and ninety-seven women were eligible for the study, and 215 (54%) participants responded. An exploratory factor analysis (EFA) revealed that a three-factor structure was the most adequate solution. Three new subscales were suggested: body image investment cognition; breast and body image investment emotions; breast reflecting dysfunctional cognitive and emotional patterns of appearance investment and body image investment behaviors; breast reflecting positive ways of investing in body image. Consistent with previous findings, control over appearance is a central theme in women with breast cancer undergoing mastectomy and reconstruction. The obtained factor structure was considered similar to the original structure and three-factor solutions obtained from an American cohort of patients with breast cancer. The ASI-R has shown good psychometric properties in Swedish women undergoing mastectomy and reconstruction. Further studies on convergent validity and confirmatory factor analysis are required.